Use of a novel 4D intracardiac echocardiography catheter to guide interventional electrophysiology procedures. (28th September 2021) - Kaplan, Rachel M.; Narang, Akhil; Gay, Hawkins; Gao, Xu; Gibreal, Mohammed; Arora, Rishi; Chicos, Alexandru; Kim, Susan; Passman, Rod; Patil, Kaustubha; Pfenniger, Anna; Verma, Nishant; et al.
Abstract: Introduction: Standard two‐dimensional (2D), phased‐array intracardiac echocardiography (ICE) is routinely used to guide interventional electrophysiology (EP) procedures. A novel four‐dimensional (4D) ICE catheter (VeriSight Pro, Philips) can obtain 2D and three‐dimensional (3D) volumetric images and cine‐videos in real‐time (4D). The purpose of this study was to determine the early feasibility and safety of this 4D ICE catheter during EP procedures. Methods: The 4D ICE catheter was placed from the femoral vein in ten patients into various cardiac chambers to guide EP procedures requiring transseptal catheterization, including ablation for atrial fibrillation and left atrial appendage closure. 2D‐ and 3D‐ICE images were acquired in real‐time by the electrophysiologist. A dedicated imaging expert performed digital steering to optimize and postprocess 4D images. Results: Eight patients underwent pulmonary vein isolation (cryoballoon in seven patients, pulsed field ablation in one, additional radiofrequency left atrial ablation in one). Two patients underwent left atrial appendage closure. High quality images of cardiac structures, transseptal catheterization equipment, guide sheaths, ablation tools, and closure devices were acquired with the ICE catheter tip positioned in the right atrium, left atrium, pulmonary vein, coronary sinus, right ventricle, and pulmonary artery. There were no complications. Conclusion: This is the first experience of a novel deflectable 4D ICE catheter used to guide EP procedures. 4D ICE imaging is safe and allows for acquisition of high‐quality 2D and 3D images in real‐time. Further use of 4D ICE will be needed to determine its added value for each EP procedure type.